Heterogeneity in 14-year Dementia Incidence Between Asian American Subgroups - Mayeda, Elizabeth R; Glymour, M Maria; Quesenberry, Jr, Charles P; Whitmer, Rachel A (Alzheimer disease and associated disorders, 2017)
Asian Americans are a rapidly growing and diverse population. Prior research on dementia among Asian Americans focused on Japanese Americans or Asian Americans overall, although marked differences in cardiometabolic conditions between subgroups have been documented. We compared dementia incidence among 4 Asian American subgroups (n=8384 Chinese; n=4478 Japanese; n=6210 Filipino; n=197 South Asian) and whites (n=206,490) who were Kaiser Permanente Northern California members aged 64 years and above with no dementia diagnoses as of January 1, 2000. Dementia diagnoses were collected from medical records January 1, 2000 to December 31, 2013. Baseline medical utilization and comorbidities (diabetes, depression, hypertension, stroke, cardiovascular disease) were abstracted from medical records January 1, 1996 to December 31, 1999. We calculated age-standardized dementia incidence rates and Cox models adjusted for age, sex, medical utilization, and comorbidities. Mean baseline age was 71.7 years; mean follow-up was 9.6 years. Age-standardized dementia incidence rates were higher among whites than "All Asian-Americans" or any subgroup. Compared with Chinese (13.7/1000 person-years), dementia incidence was slightly higher among Japanese [14.8/1000 person-years; covariate-adjusted hazard ratio (adjusted-HR)=1.08; 95% confidence interval (CI), 0.99-1.18] and Filipinos (17.3/1000 person-years; adjusted-HR=1.20; 95% CI, 1.11-1.31), and lower among South Asians (12.1/1000 person-years; adjusted-HR=0.81; 95% CI, 0.53-1.25). Future studies are needed to understand how immigration history, social, environmental, and genetic factors contribute to dementia risk in the growing and diverse Asian American population.